E-LKPD Based on APOS Theory to Improve Procedural Fluency of Grade IV Elementary School Students - Padmayani, Made Daniaraga; Agustika, Gusti Ngurah Sastra; Sutyaningsih, Anak Agung Ayu Dewi (International Journal of Language and Literature, 2025)
The problem faced in learning mathematics in grade IV of elementary school is the difficulty of students in understanding and applying mathematical procedures correctly. This study aims to develop E-LKPD based on APOS Theory to improve students' procedural fluency. The development model used is Research and Development (R&D) with the ADDIE model (analyze, design, development, implementation, evaluation). The subjects of the study were 28 grade IV students. The methods and instruments for data collection used observation, interviews, questionnaires and essay tests. Data analysis techniques used quantitative and qualitative analysis. The main results of this study indicate that the use of E-LKPD based on APOS theory can significantly improve the procedural fluency of grade IV elementary school students. After going through the validation stages, limited trials, and large-scale implementation, it was found that students who used this E-LKPD showed an increase in their ability to solve problems that require procedural steps sequentially and correctly. So it can be concluded that E-LKPD based on APOS theory to improve procedural fluency is very feasible and effective to be used in the learning process because it can improve the learning outcomes of grade IV students. The implication of this study is the importance of developing theory-based learning media to support students' procedural understanding in mathematics learning.